UNIT 14.12 The History and Use of Human Hepatocytes for the Treatment of Liver Diseases: The First 100 Patients. Issue 1 (6th November 2014) - Hansel, Marc C.; Gramignoli, Roberto; Skvorak, Kristen J.; Dorko, Kenneth; Marongiu, Fabio; Blake, William; Davila, Julio; Strom, Stephen C.
Abstract : Orthotopic liver transplantation remains the only curative treatment for many end‐stage liver diseases, yet the number of patients receiving liver transplants remains limited by the number of organs available for transplant. There is a need for alternative therapies for liver diseases. The transplantation of isolated hepatocytes (liver cells) has been used as an experimental therapy for liver disease in a limited number of cases. Recently, the 100 th case of hepatocyte transplantation was reported. This review discusses the history of the hepatocyte transplant field, the major discoveries that supported and enabled the first hepatocyte transplants, and reviews the cases and outcomes of the first 100 clinical transplants. Some of the problems that limit the application or efficacy of hepatocyte transplantation are discussed, as are possible solutions to these problems. In conclusion, hepatocyte transplants have proven effective particularly in cases of metabolic liver disease where reversal or amelioration of the characteristic symptoms of the disease is easily quantified. However, no patients have been completely corrected of a metabolic liver disease for a significant amount of time by hepatocyte transplantation alone. It is likely that future developments in new sources of cells for transplantation will be required before this cellular therapy can be fully implemented and available for large numbers of patients. © 2014 by John Wiley & Sons, Inc.